The Politics of Governing African Urban Spaces - Edgar Pieterse (Revue Internationale de Politique de Développement, 2018)
Drawing on the author’s direct experiences in urban policy formulation processes on various scales, this chapter makes a case for a more intimate reading and account of macro policy shifts that may hold the potential to advance transformative politics on the national and the urban scale. It argues that new policy concepts and frameworks can advance a more focused politics based on an analysis of the nature and terms of infrastructure investments and considers whether such investments are advancing a more inclusive, labour intensive and sustainable pattern of development in African cities and towns. The chapter asserts that urban governance policy discourses are now connecting urban investments and regulation with macroeconomic imperatives, which could lead to a greater awareness of urban governance within centres of state power. Structurally the chapter identifies examples of policy artefacts on the global, pan-African and national scales to demonstrate the shared potential for a new kind of transformative politics. Thereafter, the chapter sets out a potential methodological register to track, analyse and engage these processes on the urban scale in order to arrive at a propositional sensibility with regard to governing diverse spaces. It calls for a form of research and analysis that is not merely evaluative, after the fact, but rather positioned in the processes of unfolding. There are not enough of these kinds of scholarly accounts that can enrich and deepen debates about the politics and practice of multi-scalar urban governance reform in diverse African settings.